EXAMINING NETIZENS' VIEWS ON INDONESIAN MUSLIM CELEBRITIES’ WILDLIFE FASHION ON SOCIAL MEDIA - Mufti Rasyid (Profetik: Jurnal Komunikasi, 2023)
This study examines social media users' views on Indonesian Muslim celebrities' who use wild animal materials in fashion. Using a descriptive qualitative method, the researcher utilized Teun van Dijk's critical discourse analysis, which consists of three levels: text level (microstructure), social cognition (superstructure), and social context (macrostructure). The subject of this research was Instagram accounts and YouTube videos of Angel Lelga, Ola Ramlan, and Syahrini wearing wild-animal fashion items. The results found that in the microstructure level, the comments' word choices, emphasis, and details represent commenters' background, intention, and presumption, mostly influenced by halal-lifestyle. In the superstructure level, it can be concluded that most netizens do not understand animal welfare issues sufficiently. Meanwhile, in the  macrostructure, the researcher underlines the notion of power and access, which enables Indonesian Muslims to create a discourse on the halal lifestyle without concerning animal welfare. However, the awareness of animal welfare is also noteworthy, although not significant.